2002
DOI: 10.1002/1521-396x(200206)191:2<409::aid-pssa409>3.0.co;2-h
|View full text |Cite
|
Sign up to set email alerts
|

Positron Annihilation Study in the Early Stage of Fatigue in Type 304 Stainless Steel

Abstract: Subject classification: 61.72.Ji; 62.20.Mk; 78.70.Bj; S1.1Positron annihilation lifetime and Doppler broadening measurements have been performed to study the early stage of fatigue in type 304 stainless steel at various positions of samples at room temperature. Both the average lifetime of positron and the S parameter have increased with increasing number of fatigue cycles at each position. From two-lifetime component analysis, the component of the longer lifetime of about 170 ps, corresponding to single or di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Furthermore, in [104], it was reported that the positron lifetime did not exhibit significant change after 50% of the lifetime in the SS 316L. Similar studies reporting early saturation have also been performed on SS 304 [109,110].…”
Section: S − Parameter =mentioning
confidence: 63%
“…Furthermore, in [104], it was reported that the positron lifetime did not exhibit significant change after 50% of the lifetime in the SS 316L. Similar studies reporting early saturation have also been performed on SS 304 [109,110].…”
Section: S − Parameter =mentioning
confidence: 63%